Time-varying non-uniform temperature distributions in concrete box girders caused by solar radiation in various regions in China. (February 2022) - Sheng, Xingwang; Shi, Tao; Zheng, Weiqi; Lou, Ping
Non-uniform temperature distributions of concrete box girders are induced by solar radiation depending on the structural shapes and shadows cast on them. Using a real-time shadow-selection algorithm and finite element method, the thermodynamic analysis of concrete box girders is carried out to simulate their time-varying temperature distributions. The theoretical results of the finite element model (FEM) are verified by measured data. Based on this, a series of FEMs of concrete box girders are established considering regional influences, and the temperature gradients of concrete box girders in different climatic zones in China are studied. The most unfavorable temperature gradient of concrete box girders in China is obtained, and it is important for design and not only for health monitoring. Moreover, comparing the temperature gradient modes in the specifications of various countries, the temperature gradient of concrete box girders in the China Highway Bridges Design Code is conservative for structural design. Furthermore, the influences on structural temperature distributions of varying environmental factors induced by regional influences are explored, including atmospheric transparency coefficient (ATC) and solar radiation absorptivity (SRA).